Implementasi Kebijakan Smart City Pada Pelayanan Publik Di Bidang Kesehatan: Studi Kasus Rumah Sakit Umum Kota Tarakan - Febi; Lutfi Wahyudi (Jurnal Ilmu Pemerintahan, 2026)
The advancement of information technology in the Industrial Revolution 4.0 era has encouraged the government to adopt digital-based policies through the Smart City concept to enhance the effectiveness, efficiency, and transparency of public services, including healthcare. Tarakan City, as one of the regions included in the 100 Smart City Movement program, implements this initiative at Tarakan City General Hospital (RSUKT) to realize responsive and community-oriented health services. This study analyzes the implementation of the Smart City policy in public health services at RSUKT using George C. Edwards III’s policy implementation theory, which emphasizes communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method with a case study approach was applied, and data were obtained through interviews, observations, and documentation, validated using triangulation techniques. The results show that the Smart City policy positively improves the quality of services at RSUKT; inter-unit communication runs adequately, digital facilities and infrastructure are available though human resource competencies still require improvement, implementers demonstrate supportive attitudes, and the bureaucratic structure supports service delivery through well- standardized SOPs. However, digital literacy among patients and the need for ongoing digital training for health workers remain challenges. Overall, the Smart City policy in Tarakan City has enhanced the effectiveness and efficiency of public health services, but long-term sustainability requires strengthening human resource capacity and improving public digital literacy.